(untitled) (Journal of Technology and Operations Management, 2013)
Green business management and green supply chain practices are drivers to sustainability of environment in which the organizations use to take care in their business operations. The research is conducted as a case study in a manufacturing organization that located in Shah Alam, Selangor. The research is trying to explore the organization’s understanding about green business management practices and green supply chain implementation as well as the impacts on the organization. The research is applying a qualitative method where a few informants were selected for face-to-face semi structured interviews. In addition, some observations were made including photo collections. From the data analysis, we can see that the organization is applying some of green business management practices such as recycle bins, e-mail reminder, saving energy appliances, planting of trees, telecommuting, green team and green logistics. As overall, the results of green business management practices and green supply chain have improved organization’s reputation and operations efficiency via cost savings of recycling procedures, minimizing wastes, reducing energy and improvement towards the employee’s health issues.